Par-1 and PP2A: Yin-Yang of Bazooka localization. - Choi, K.W.; Nam, S.C.; Mukhopadhyay, B. (Fly, 2007)
Apical basal cell polarity is a fundamental feature of all epithelial cells. Identification of the genes involved in the polarization of epithelial cells has begun to reveal the mechanisms underlying the establishment and maintenance of cell polarity. An important issue is to understand the molecular basis for localization of cell polarity proteins in the context of the developing organism. Bazooka (Baz, Drosophila homolog of Par-3) plays a crucial role in organizing cell polarity in several different tissues. In the ovarian follicle epithelium, Par-1 protein kinase regulates Baz localization to the apical cell cortex by excluding phosphorylated Baz from the lateral region. In photoreceptor cells of retinal epithelium, Baz is targeted to the adherens junction (AJ) instead of the apical domain. Our study suggests that in photoreceptors, Par-1 blocks the localization of Baz to AJ whereas protein phosphatase 2A (PP2A) promotes Baz localization by antagonizing the Par-1 effects. In this extra view, we provide a brief overview and perspective of our findings on the antagonistic function of Par-1 and PP2A in Baz localization during photoreceptor morphogenesis.